2009
DOI: 10.1007/s00787-009-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Does inhibitory control capacity in overweight and obese children and adolescents predict success in a weight-reduction program?

Abstract: It has been assumed that inhibitory control capacity might influence the success of overweight or obese subjects in reducing weight. However, empirical research on this association is scarce. The present study, therefore, examines whether success in an outpatient weight-reduction program for children and adolescents can be predicted by pre-intervention inhibitory control capacity. The study sample consisted of 111 overweight and obese children and adolescents (7.5-15 years) who attended an outpatient weight-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 28 publications
6
58
1
1
Order By: Relevance
“…However, this finding seems in sharp contrast with several studies linking impulsivity to a greater chance of relapse (Doran, Spring, McChargue, Pergadia, & Richmond, 2004;Yoon et al, 2007), and with a study suggesting impulsivity interferes with weight loss (Nederkoorn et al, 2007). There are also a few reports, however, linking impulsivity with a reduced risk of relapse after treatment (Papachristou, Nederkoorn, Giesen, & Jansen, 2014;Pauli-Pott, Albayrak, Hebebrand, & Pott, 2010). One intriguing possibility is that those treatments and the current extinction procedure targeted similar underlying mechanisms that the impulsives (who may need it the most) benefitted most from.…”
Section: Individual Differences In Conditioningcontrasting
confidence: 52%
See 1 more Smart Citation
“…However, this finding seems in sharp contrast with several studies linking impulsivity to a greater chance of relapse (Doran, Spring, McChargue, Pergadia, & Richmond, 2004;Yoon et al, 2007), and with a study suggesting impulsivity interferes with weight loss (Nederkoorn et al, 2007). There are also a few reports, however, linking impulsivity with a reduced risk of relapse after treatment (Papachristou, Nederkoorn, Giesen, & Jansen, 2014;Pauli-Pott, Albayrak, Hebebrand, & Pott, 2010). One intriguing possibility is that those treatments and the current extinction procedure targeted similar underlying mechanisms that the impulsives (who may need it the most) benefitted most from.…”
Section: Individual Differences In Conditioningcontrasting
confidence: 52%
“…This result is in contrast with a study reporting negative relationships between impulsivity and weight loss success (Nederkoorn et al, 2007), and with several addiction studies showing positive associations between impulsivity and risk of relapse (e.g., Doran, Spring, McChargue, Pergadia, & Richmond, 2004;Yoon et al, 2007). However, we have previously found impulsivity to moderate reacquisition of conditioned desires in precisely the manner reported here (van den Akker et al, 2014, study 2), and, in fact, some studies have associated higher impulsivity with lower relapse rates after treatment and greater benefits from a weight reduction program in overweight children (Papachristou, Nederkoorn, Giesen, & Jansen, 2014;Pauli-Pott, Albayrak, Hebebrand, & Pott, 2010). The authors suggested that their impulsive participants might have benefitted more from certain aspects of the behaviour modification therapies that they had received, and one could speculate that the present extinction procedures have tapped into similar underlying constructs.…”
Section: Discussionmentioning
confidence: 46%
“…31 ADHD symptoms were shown to be strong negative predictors of intentional weight loss in all previous studies 11,32,33 except for one. 34 Thus, while adolescent girls with low ADHD symptoms may have better chances to achieve normal weight, those with high ADHD symptoms might tend to fail and remain overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of impulsivity on treatment course, data are contradictory. 43,44 Other data pointing to the role of impulsivity demonstrated that overweight children reached higher scores in delinquent problems and were evaluated by peers as being more aggressive and disruptive than non-overweight children. 45,46 Not only poor inhibitory control, but also reward sensitivity, another aspect of impulsive behavior, has been linked to childhood obesity or overeating.…”
Section: 25mentioning
confidence: 99%